The Huk rebellion a study of peasant revolt in the Philippines - Kerkvliet, Benedict J. (University of California Press, 1977)
Newly available with an updated bibliographic essay, this highly acclaimed work explores the Huk rebellion, a momentous peasant revolt in the Philippines. Unlike prevailing top-down analysis, Kerkvliet seeks to understand the movement from the point of view of its participants and sympathizers. He argues that seeing a peasant revolt through the eyes of those who rebelled explains and clarifies the actions of people who otherwise might appear irrational. Drawing on a rich array of documents and in-depth interviews with peasants and rebel leaders, the author provides definitive answers to the causes of the rebellion, the goals of the rebels, and the process of resistance.